Pengelolaan Plasma Nutfah Tanaman Terintegrasi dengan Program Pemuliaan - nFN Sumarno; Nani Zuraida (Buletin Plasma Nutfah, 2008)
Plant breeding, as an applied of plant genetics, is based and is supported by various subdisciplines of genetic sciences, includeing plant germplasm, classical genetics, molecular genetics, cytogenetics, gene-transformation techniques, etc. Linkage and team work system between plant germplasm management and plant breeding program is most required, since the success of plant breeding maybe obtained from the contribution of gene donor parents, derived from the germplasm management. Without the flow of genes from the germplasm collection, varieties produced by the plant breeder would suffer a narrow genetical based or a bottle-necking genetic based. Plant germplasm research is an integral part of the germplasm management, aimed to (1) evaluate the genetic variation of the germplasm collection, to be readily available for the breeding program and to be used for scientific publications, (2) tracing the origin of plant species, and (3) officially release a selected germplasm, containing new economic gene (s). The linkage between germplasm management and plant breeding research program could be facilitated through the following activities (1) identifying an elit germplasm for varietal release, (2) selection and stabilization of a promising germplasm accession for possible varietal releases, (3) use of germplasm accession as a gene donor parent to incorporate adaptive genes into improved variety, (4) use of germplasm accession for a specific donor gene, (5) use of germplasm to broaden the genetical base of varieties through an introgression and nobilization, (6) use of germplasm to improve the genetic value of the breeding population, and (7) to develop multiple crossess involving many parents to broaden the genetical base of the breeding population. Another important function of the germplasm management is to conserve accessions carrying genes which may be useful in the future, to anticipate the dynamic changing of biological and environmental stresses on crop. Germplasm management is considered successfully conducted when it is continously supplying donor gene parents to breeders for parental crosses on their breeding program, conversely, breeding program in considered successfully managed, when it uses the rich genetic variability available on the germplasm collection. Separating the organizational units among the breeding program, germplasm management and molecular genetic research, is only for enhancing the intensity of the research, but should not separate the linkage program of the research. AbstrakPemuliaan tanaman merupakan ilmu genetika terapan yang didukung oleh berbagai cabang ilmu kegenetikaan, termasuk plasma nutfah, genetika klasik, genetika molekuler, sitogenetika, dan genetika transformasi. Keterpaduan antara pengelolaan plasma nutfah dengan pemuliaan tanaman tidak dapat ditawar, karena keberhasilan pemuliaan sangat tergantung dari ketersediaan sumber gen yang disediakan oleh pengelola plasma nutfah. Tanpa kontribusi sumber gen dari pengelola plasma nutfah, hasil pemuliaan tanaman mengalami penyempitan kandungan genetik, atau terjadi gejala leher botol genetik. Penelitian plasma nutfah merupakan bagian integral dari pengelolaan materi plasma nutfah, bertujuan untuk (1) menggali kekayaan sifat genetik plasma nutfah guna penyediaan tetua persilangan dan bahan publikasi ilmiah, (2) menelusuri asal-usul spesies tanaman, (3) melepas secara resmi plasma nutfah sebagai sumber gen yang diakui kepemilikannya. Keterkaitan pengelolaan plasma nutfah dengan program pemuliaan dapat dilaksanakan melalui (1) pemanfaatan langsung aksesi plasma nutfah elit untuk dilepas sebagai varietas unggul, (2) pemurnian dan pemantapan populasi aksesi plasma nutfah sebagai calon varietas, (3) pemanfaatan aksesi plasma nutfah sebagai donor gen untuk rekombinasi gen-gen unggul adaptif, (4) plasma nutfah sebagai donor gen spesifik, (5) plasma nutfah sebagai bahan perluasan latar belakang genetik varietas melalui proses introgresi dan nobilisasi, (6) pemanfaatan plasma nutfah untuk perbaikan genetik populasi seleksi, dan (7) pembentukan populasi dasar yang mengandung keragaman genetik luas melalui persilangan banyak tetua. Fungsi pengelolaan plasma nutfah lainnya adalah melestarikan sumber daya genetik untuk kebutuhan gen di masa depan, agar dapat menyediakan gen-gen untuk mengantisipasi perubahan ras patogen dan tipe baru serangga hama yang bersifat dinamis, serta penyediaan gen guna mengatasi cekaman abiotik alamiah. Pengelolaan plasma nutfah dinilai berhasil apabila telah mampu menyediakan aksesi plasma nutfah sebagai sumber gen donor dalam program pemuliaan. Pemuliaan tanaman berhasil secara optimal apabila telah memanfaatkan keragaman genetik sifat yang diinginkan, yang tersedia dalam koleksi plasma nutfah. Keterpisahan kelembagaan antara unit kerja pengelolaan plasma nutfah dengan program pemuliaan tidak boleh membatasi keterpaduan program penelitian antara kedua cabang disiplin keilmuan tersebut.